Soutenir le cheminement de stage d'apprentis enseignants au secondaire par un environnement d'apprentissage hybride / Supporting the advancement of student-teachers in their practica with the use of a hybrid learning environment - Stéphane Allaire (The Canadian Network for Innovation in Education (CNIE), 2009)
Résumé : Dans un contexte de pratiques éducatives en renouvellement, la recherche participative étudie l'apport d'un environnement d'apprentissage hybride pour l'analyse réflexive de stagiaires en enseignement secondaire. Des analyses qualitatives et quantitatives descriptives illustrent le potentiel des dispositifs mis en place pour soutenir l'intégration à un contexte de stage innovateur, une réflexivité diversifiée et la coélaboration de connaissances. Abstract : In the context of evolving educational practices, participatory research is used to study the contribution of a hybrid learning environment when used by student teachers in secondary teaching for reflective analysis. Both quantitative analysis and qualitative descriptives illustrate the potential of the devices and strategies used to support the student teachers in their integration into an innovative practicum context, a diversified reflective practice and knowledge building.